BLEED: a classification tool to predict outcomes in patients with upper and lower gastrointestinal hemorrhage - Huchchannavar, Suresh; Puttannavar, Girish; Hebsur, Narayanchandra I. (International Surgery Journal, 2017)
Background: Acute gastrointestinal (GI) haemorrhage is a common clinical problem with diverse manifestations. Such bleeding may range from trivial to massive and can originate from virtually any region of the GI tract, including the pancreas, liver, and biliary tree. Several risk scoring systems have also been proposed to classify patients into high and low risk groups for complications, like re-bleeding or mortality, based on multivariate analyses. Kollef and colleagues identified the BLEED criteria: (a) ongoing Bleeding, (b) Low systolic blood pressure (BP), (c) Elevated prothrombin time (PT), (d) Erratic mental status, and (e) unstable comorbid Disease as risk factors for complication of GIH at any time during hospitalization after an initial 24 hours of stabilization. The objective of this study was to predict outcome according to a risk stratification BLEED criterion, independent of endoscopic findings. Methods: We studied all patients who presented with acute gastrointestinal bleeding to emergency department. patients with epistaxis, paranasal sinuses bleed, upper GI bleed secondary to endoscopic procedure, patients with chronic Anemia and those patients which admitted with Primary diagnosis other than UGIB were excluded. Patients meeting the BLEED criteria at their initial assessment were classified as high risk (66) and all others were categorized as low-risk (10). In-hospital complications were defined as recurrent UGIB, surgery to control the source of hemorrhage, hospital mortality, length of hospital stay and units of blood transfused. Results: There were 76 patients, with mean age of 46.37 years, 56 patients (73.3%) were case of Upper gastrointestinal bleeding, 20 patients (26.7%) were case of lower gastrointestinal bleeding. 66 (86.84%) of patients were categorized as high-risk patients and 10(13.2%) of patients were categorized as low risk patients. 14(21.1%) of patients were admitted in ICU ,13 Patients had undergone surgery (17.10%), 1 (1.5%) of patient had Re bleeding, nine (13%) had died. Stastical analysis showed significant association between components like low SBP (P=0.008), elevated prothrombin time (P=0.04), erratic mental status(P=0.001) and in hospital complications. All nine deaths were found in high risk group. Conclusions: BLEED criteria can be used as triage tool for stratifying the patients of acute gastrointestinal haemorrhage into high risk and low risk category without endoscopic findings and useful in predicting outcome in such patients and plan the treatment accordingly.